UJI VALIDITAS MODUL MEDIA PEMBELAJARAN BUSY BOX SEX EDUCATION UNTUK MENINGKATKAN PENGETAHUAN PENDIDIKAN SEKSUAL DI SLB HARAPAN MULIA KOTA JAMBI: VALIDITY TEST OF THE BUSY BOX SEX EDUCATION LEARNING MEDIA MODULE TO IMPROVE KNOWLEDGE OF SEXUAL EDUCATION FOR MILD MENTALLY RETARDATED CHILDREN AT SLB HARAPAN MULIA JAMBI CITY - Erna Yulianti; Dessy Pramudiani (Jurnal Psikologi Jambi, 2021)
Introduction Mild mentally retarded children experience sexual development like normal individuals. In principle, the material for sexual education taught is the same as for normal children with the presentation of material that is adjusted to the condition of the child's intelligence level and age. This module to facilitate children with mild mental retardation in learning knowledge of sexual education needs to be stimulated using 4 stages in the Busy Box Sex Education module. Method This study aims to test the validity of the Busy Box Sex Education module to increase sexual knowledge of children with mild mental retardation. The type of research used is module validation research. This study used 4 validators who were determined based on a purposive technique to test the suitability of the module content with the objectives to be achieved. Data analysis used descriptive analysis using Aiken's V (validation sheet). Results The aiken's V score showed a range of 0.56 - 0.88 and the results of the validation of the aiken's V score of 0.50 - 0.88. Based on the validity test, the contents of the Busy Box Sex Education module were considered valid by the validator criteria with several suggestions for improvement. Conclusion And Recommendation Based on the results of the module content validity test, it can be concluded that the Busy Box Sex Education module is at a good validity level. Keywords: Module Validity, Sexual Education, Busy Box Sex Education. ABSTRAK Pendahuluan Anak tunagrahita ringan mengalami perkembangan seksual seperti individu normal. Materi pendidikan seksual yang diajarkan pada prinsipnya sama seperti anak normal dengan penyajian materi yang disesuaikan dengan kondisi tingkat kecerdasan dan usia anak. Untuk memfasilitasi anak tunagrahita ringan dalam mempelajari pengetahuan pendidikan seksual perlu distimulasi menggunakan 4 tahapan dalam modul busy box sex education. Metode Penelitian ini bertujuan untuk menguji validitas modul busy box sex education untuk meningkatkan pengetahuan seksual anak tunagrahita ringan. Jenis penelitian yang digunakan yaitu riset validasi modul. Penelitian ini menggunakan 4 orang validator yang ditentukan berdasarkan teknik purposive untuk menguji kesesuaian isi modul dengan tujuan yang hendak dicapai. Analisis data menggunakan analisis deskriptif dengan menggunakan Aiken’s V (lembar validasi). Hasil Angka skor aiken’s V menunjukkan rentang 0.56 – 0.88 dan hasil validasi alat ukur skor aiken’s V 0.50 – 0.88. Berdasarkan hasil uji validitas isi modul busy box sex education yang dinilai validator termasuk dalam kriteria valid dengan beberapa saran perbaikan. Kesimpulan dan Saran Berdasarkan hasil uji validitas isi modul dapat disimpulkan bahwa modul busy box sex education berada pada tingkat validitas yang baik. Kata Kunci: Validitas Modul, Pendidikan Seksual, Busy Box Sex Education